Characterization of a New Allele of the Saponin‐Synthesizing Gene Sg‐1 in Soybean. Issue 1 (1st January 2016) - Park, Jiho; Kim, Jeong Hwa; Krishnamurthy, Panneerselvam; Tsukamoto, Chigen; Song, Jong Tae; Chung, Gyuwha; Shannon, J. Grover; Lee, Jeong‐Dong
ABSTRACT: Saponins are major components of secondary metabolites in soybean [ Glycine max (L.) Merr.] seed that have been broadly studied for their beneficial effects on human health. In soybean, group A acetylsaponins can be classified into two types: Aa‐ and Ab‐series, both of which cause bitter and astringent aftertaste. Therefore, group A acetylsaponin‐deficient cultivars can solve a problem that has inhibited the broader use of soybean in the food industry. The objective of this study was to investigate a group A acetylsaponin‐deficient soybean mutant (PE1515) generated from the cultivar Pungsannamul (containing Ab‐series saponins) by ethyl methanesulfonate treatment. The phenotypic and genotypic variation was investigated for the mutant PE1515. Our analyses showed that in soybean line PE1515, the Ab‐series saponins were absent and A0‐αg saponin accumulated as the major saponin. PE1515 had a single base substitution from G to A at 1004 bp of the Sg‐1 gene, which introduced a premature stop codon in the Sg‐1 gene. A DNA marker to detect the single nucleotide substitution was developed for breeding purposes. Based on this genetic marker, the association of the sg‐1 allele in PE1515 was tested using 120 F2 progeny of a cross Pungsannamul × PE1515. The results showed that the mutation of the Sg‐1 gene in PE1515 contributed to the lack of Ab‐series saponins in the seed hypocotyl. The soybean line PE1515, which does not produce detectable Ab‐series saponins, would be a good genetic resource to improve soybean for wider use in foods.